The brief introduction to organizational citizenship behaviors and counterproductive work behaviors: a literature review - Fan, Qianqian; Wider, Walton; Chan, Choon Kit (Frontiers in Psychology, 2023)
This paper presents a literature review on the topic of organizational performance. The study conceptualizes the overall performance of the organization as comprising of organization citizenship behaviors (OCB) and counterproductive work behaviors (CWB). While there are numerous research studies on OCB, not many have focused on how OCB and CWB affect organizational performance simultaneously. The paper provides an explanation of the OCB and CWB concepts, followed by the primary research and focus of the study. The article presents a comprehensive framework for understanding the meanings of OCB and CWB, along with an internal hierarchy. This framework will serve as a beneficial resource for working managers, academics, and researchers, who seek to optimize economic productivity through improved understanding and management of OCB and CWB.